2014
DOI: 10.1111/aec.12152
|View full text |Cite
|
Sign up to set email alerts
|

At home with the birds:Kalahari tree skinks associate with sociable weaver nests despiteAfrican pygmy falcon presence

Abstract: The way in which animals use habitat can affect their access to key resources or how they are buffered from environmental variables such as the extreme temperatures of deserts. One strategy of animals is to modify the environment or to take advantage of structures constructed by other 2 species. The sociable weaver bird (Philetairus socius) constructs enormous colonial nests in trees. These nests are frequented by Kalahari tree skinks (Trachylepis spilogaster) and the two species coexist over a large portion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Therefore, we suggest studies covering multiple years would be useful to fully evaluate the predictions of the SGH as it relates to the role of sociable weaver colonies. Furthermore, certain groups not included in this study, arthropods, amphibians and reptiles, are expected to benefit most from terrestrial engineers (Romero et al, 2015), and this is supported by studies that have shown increased abundance of invertebrates and reptiles at weaver colonies (Harvey et al, 2015;Rehn, 1965;Rymer et al, 2014).…”
Section: Colony Use Across a Seasonal Gradientmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, we suggest studies covering multiple years would be useful to fully evaluate the predictions of the SGH as it relates to the role of sociable weaver colonies. Furthermore, certain groups not included in this study, arthropods, amphibians and reptiles, are expected to benefit most from terrestrial engineers (Romero et al, 2015), and this is supported by studies that have shown increased abundance of invertebrates and reptiles at weaver colonies (Harvey et al, 2015;Rehn, 1965;Rymer et al, 2014).…”
Section: Colony Use Across a Seasonal Gradientmentioning
confidence: 65%
“…Anecdotal data suggest a wide range of non‐obligate species also associate with these colonies (Maclean, 1973a). For example, Kalahari tree skinks Trachylepis spilogaster increase in abundance at trees that host weaver colonies (Rymer et al., 2014) while African pygmy falcons Polihierax semitorquatus , and some arthropods are obligately dependent on these structures (Harvey et al., 2015; Rehn, 1965). Nevertheless, the full importance of these nest colonies to the surrounding animal community is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, coupled with the positive effect of rainfall on reproductive output (Covas et al, ; Mares et al, ), less and later rainfall would most likely result in a negative impact on population growth rate through decreased fecundity. Even though total rainfall is forecasted to decrease, extreme rainfall events are likely to continue to increase (DEA, ; Mason, Waylen, Mimmack, Rajaratnam, & Harrison, ; Niang et al, ); whether and how these projected changes affect the persistence of this keystone species (Rymer, Thomson, & Whiting, ) remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Colony presence increased the abundance of reptiles. Our findings support previous research that showed reptiles associate with weaver colonies (Rymer et al, 2014). However, we did not see variation between the differences in colony and non-colony trees across the aridity gradient.…”
Section: Abundance Of Reptilesmentioning
confidence: 99%
“…Soils directly below colonies have particularly increased nutrient levels (Prayag et al, 2020) and this could result in direct effects on the local vegetation and animals. Weaver colonies have been shown to act as a resource to multiple species within the environment (Bolopo et al, 2019; Lowney & Charlton, 2017; Maclean, 1970; Rehn, 1965; Rymer et al, 2014) and maintain this impact throughout the year (Lowney & Thomson, 2021). Their facilitative role across their distribution remains unknown (Figure 1).…”
Section: Introductionmentioning
confidence: 99%